A NEW IMAGE ENCRYPTION AND DECRYPTION ALGORITHM BASED ON A FOUR-DIMENSIONAL DYNAMIC SYSTEM - Abdulghafor Waedallah Abdulghafor; Muthana S. Mahdi; Amer Jelwy Mohammed (Journal Park Publishing, 2023)
With the rapid developments in the fields of multimedia and widespread use of the Internet, multimedia protection has become extremely necessary. Encryption, which prohibits an unauthorized individual from accessing sensitive data, is one of the best alternatives for achieving multimedia data protection that is sent over IoT devices. The chaotic systems of image cryptography have become an effective way to encrypt images in recent years due to their excellent protection. This study introduces a brand-new method for image encryption and decryption schemes. The new algorithm uses the Latin Square matrix depended based on a four-dimensional hyper-chaotic approach that achieves a security high level. The sequence chaotic generated by the system is used to diffuse and permute plain images of any size to produce encrypted images. Statistical measures have been used to analysis the Results such as the histogram, coefficient of correlation, and key sensitivity to examine the algorithm's performance. The experimental results show that the encrypted images have uniform histogram and entropy values between 7.99990 and 7.99991. The values of NPCR and UACI are close to ideal, with NPCR at 99.6825 percent and UACI at 33.4778 percent. Moreover, the method is robust against statistical, predictive, differential, and brute-force assaults because of its strong encryption performance, huge key space of 10168, and great sensitivity to small changes in the secret key.
Keywords: Four-Dimensional (4D) Hyper-Chaotic Systems, Cryptography, Image Encryption in IoT, Multimedia Security, New Algorithm.